1998
DOI: 10.1007/s004230050106
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life after treatment of pancreatic cancer

Abstract: In the past decade there has been increasing focus on assessment of the quality of life (QoL) of patients with cancer. QoL is now a mandatory endpoint in many cancer clinical trials, particularly in interventions with palliative intent alone. Although QoL is difficult to define, a variety of specially designed and validated questionnaires has been developed to measure QoL in the clinical setting. In pancreatic cancer, assessment (QoL) is of paramount importance; however, little research has been conducted and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 22 publications
1
22
0
2
Order By: Relevance
“…Finally, radiotherapy was associated with chronic radiation dermatitis, chronic diarrhea, and strictures/obstruction. These findings are consistent with previous studies with patient-reported outcomes, many of which utilize the QLQ-PAN26, an EORTC-affiliated disease-specific quality of life questionnaire (10)(11)(12)(13). The use of patient-reported outcomes is especially important in cancers with poor prognoses to ensure that any intervention to extend survival is undertaken in a meaningful manner, as judged by the patients themselves.…”
Section: Discussionsupporting
confidence: 87%
“…Finally, radiotherapy was associated with chronic radiation dermatitis, chronic diarrhea, and strictures/obstruction. These findings are consistent with previous studies with patient-reported outcomes, many of which utilize the QLQ-PAN26, an EORTC-affiliated disease-specific quality of life questionnaire (10)(11)(12)(13). The use of patient-reported outcomes is especially important in cancers with poor prognoses to ensure that any intervention to extend survival is undertaken in a meaningful manner, as judged by the patients themselves.…”
Section: Discussionsupporting
confidence: 87%
“…QOL assessment in pancreatic diseases, both malignant and benign, is still in the early stages of data retrieval and evaluation, and there are many opportunities for future research and development. 34 Additional studies incorporating both preoperative and serial postoperative QOL assessment are needed. Studies are also needed to evaluate QOL for the various nonsurgical management strategies in pancreatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Fitzsimmons and Johnson [16] accounted a 25-fold increase in the number of references in the literature to QoL in pancreatic cancer. Of 78 papers reviewed, only 9 used a previously validated QoL questionnaire.…”
Section: Quality Of Life In Surgery For Pancreatic Cancermentioning
confidence: 99%
“…Little research has been conducted to support or disprove such assumptions. An assessment of the effect of such interventions on QoL is urgently required in a second step in a randomized controlled trial [16].…”
Section: Quality Of Life In Surgery For Pancreatic Cancermentioning
confidence: 99%